Futures of Science and Technology in Society - Rip, Arie (Technikzukünfte, Wissenschaft und Gesellschaft / Futures of Technology, Science and Society, 2018)
Longer-term developments shape the present and endogenous futures of institutions and practices of science and technology in society and their governance. Understanding the patterns allows diagnosis and soft intervention, often linked to scenario exercises. The book collects six articles offering key examples of this perspective, addressing ongoing issues in the governance of science and technology, including nanotechnology and responsible research and innovation; and it adds two more articles that address background philosophical issues. Contents Protected Spaces of Science: Their Emergence and Further Evolution in a Changing World.- Science Institutions and Grand Challenges of Society: A Scenario.- Processes of Technological Innovation in Context - and Their Modulation.- De facto Governance of Nanotechnologies.- Constructive Technology Assessment.- Past and Future of Responsible Research and Innovation.- Technology as Prospective Ontology.- Interlocking Sociotechnical Worlds. Target Groups Scholars and advanced students in science and technology studies and in science, technology and innovation policy studies.- Technology assessment practitioners.- Policy makers and agency staff.- Journalists The Author Arie Rip is Emeritus Professor of Philosophy of Science and Technology in the School of Management and Governance of the University of Twente.